THE INFLUENCE OFiWORKiMOTIVATION ANDiCOMPETENCE ONiEMPLOYEE PERFORMANCEiIN MIDDLE SCHOOLS VOCATIONAL SCHOOL (SMK) – MIDDLE SCHOOL CHEMICAL ANALYSIS (SMAK) MAKASSAR - febrianti nur; Musran Munizu; Wahdah (Scientium Management Review, 2023)
Human resources or employees areian important factorifor everyiorganization, becauseiwithout humaniresources theigoals andiobjectives ofian organizationior companyiwill notibe achievedias planned. Humaniresources areinot onlyiseen asian elementiof productionibut alsoias humansiwho haveiemotions andipersonalities thatican beiused as aiforce toidrive aniorganization oricompany. Theipurpose ofithis studyiwas toianalyze theieffect ofiwork motivationiand competenceion employeeiperformance atiSMK - SMAK Makassar City. Theitotal populationiin thisistudy were alliemployees ofiMakassar CityiVocational High Schools, totaling 59 people. Theisample usediin thisistudy isithe entireipopulationiof 59 people because theitotal population is below 100. This researchiwas conductediusing aisurveyiapproach, theitype ofiresearch conductediwasidescriptive quantitative. Dataicollection wasicarried outiusingiquestionnaires, literatureiand observation. Data analysisiused descriptiveiand inferentialistatistics (multipleilinear regression). Theiresults ofithis studyiindicate thatisimultaneously theivariables ofiwork motivationiand competence haveia positiveiand significantieffect oniemployee performanceiat SMK - SMAK Makassaricity. While partially, workimotivation hasia positiveiand significantieffect oniemployeeiperformance. Likewise, competenceihas aipositive andisignificant effection employeeiperformance. Data analysisiused descriptiveiand inferentialistatistics (multipleilineariregression). Theiresults ofithis studyiindicate thatisimultaneouslyithe variables ofiwork motivationiand competenceihave a positiveiand significantieffect oniemployee performanceiat SMK - SMAKiMakassar city. While partially, workimotivation hasia positiveiand significantieffect oniemployee performance. Likewise, competenceihas aipositive andisignificant effection employeeiperformance. Data analysisiused descriptiveiand inferentialistatistics (multipleilinear regression). Theiresults ofithis studyiindicate thatisimultaneously theivariables ofiwork motivationiand competenceihave a positiveiand significantieffect oniemployee performanceiat SMK - SMAK Makassaricity. While partially, workimotivation hasia positiveiand significantieffect oniemployeeiperformance. Likewise, competenceihas aipositive andisignificant effection employeeiperformance.